2018
DOI: 10.1002/cplu.201800103
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Coordination Chemistry of 1,4,7‐Triazacyclononane for Biomimicry and Radiopharmaceutical Applications

Abstract: 1,4,7‐Triazacyclononane (TACN)‐based mono‐ and poly‐nuclear metal complexes have found extensive use as biological mimics for understanding the structural and operational aspects of complex natural systems. Their coordination flexibility has also provided researchers access to a vast library of radiometal‐binding motifs that display excellent thermodynamic stability and kinetic inertness upon metal complexation. Synthetic modification of the TACN backbone has yielded ligands that can form metal complexes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 105 publications
0
40
0
Order By: Relevance
“…Unlike these previous studies, considerable amounts of radioactivity were this time also found in the liver of the animals, resulting in a kidney‐to‐liver ratio of 1.7 ± 0.2 and 3.0 ± 0.6 for CTRL‐dPG and α‐EGFR‐dPG, respectively. Radiometal release from the chelator and transchelation could be one reason behind the observed liver accumulation, although the used chelator DMPTACN possesses excellent kinetic stability with Cu 2+ ions . Released radiocopper from an i.v.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Unlike these previous studies, considerable amounts of radioactivity were this time also found in the liver of the animals, resulting in a kidney‐to‐liver ratio of 1.7 ± 0.2 and 3.0 ± 0.6 for CTRL‐dPG and α‐EGFR‐dPG, respectively. Radiometal release from the chelator and transchelation could be one reason behind the observed liver accumulation, although the used chelator DMPTACN possesses excellent kinetic stability with Cu 2+ ions . Released radiocopper from an i.v.…”
Section: Resultsmentioning
confidence: 99%
“…[17] Dual-labeled dPGfunctionalized cyanine dyes for fluorescence imaging and sdAbs for targeting, respectively, were prepared in an one-pot reaction following a previously described protocol with some modifications (Scheme 1). [18] Small 2020, 16,1905013 Scheme 1. Synthesis of dual-labeled nanomaterials.…”
Section: Preparation Of Dual-labeled Dendritic Polyglycerolsmentioning
confidence: 99%
See 3 more Smart Citations